On fear and nuclear terrorism. (March 2015) - Weiss, Leonard
Fear of nuclear weapons is rational, but its extension to terrorism has been a vehicle for fear-mongering that is unjustified by available data. The debate on nuclear terrorism tends to distract from events that raise the risk of nuclear war, the consequences of which would far exceed the results of terrorist attacks. And the historical record shows that the war risk is real. The Cuban Missile Crisis and other confrontations have demonstrated that miscalculation, misinterpretation, and misinformation could lead to a "close call" regarding nuclear war. Although there has been much commentary on the interest that Osama bin Laden, when he was alive, reportedly expressed in obtaining nuclear weapons, evidence of any terrorist group working seriously toward the theft of nuclear weapons or the acquisition of such weapons by other means is virtually nonexistent. The acquisition of nuclear weapons by terrorists requires significant time, planning, resources, and expertise, with no guarantees that an acquired device would work. It requires putting aside at least some aspects of a group's more immediate activities and goals for an attempted operation that no terrorist group has accomplished. While absence of evidence does not mean evidence of absence, it is reasonable to conclude that the fear of nuclear terrorism has swamped realistic consideration of the threat.